2011
DOI: 10.3892/ol.2011.338
|View full text |Cite
|
Sign up to set email alerts
|

Genistein inhibits placental choriocarcinoma cell line JAR invasion through ERβ/MTA3/Snail/E-cadherin pathway

Abstract: Abstract. Genistein, the most abundant phytoestrogen in soybeans, may bind to estrogen receptors and perform anticancer activities. Choriocarcinoma is a malignant, trophoblastic and aggressive cancer of the placenta. Few studies are currently available concerning the effects of genistein on choriocarcinoma. In the present study, we investigated the effect of genistein on the invasive potential of the choriocarcinoma cell line JAR and its underlying mechanism. Our data revealed that genistein inhibited JAR cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…Genistein, which is abundantly found in soybean, is anti-proliferative cancer cell. Genistein is a potent inhibitor of tyrosine kinase, which is involved in proliferation signal cascades of cell growth (5), and moderate doses of genistein have been found to have inhibitory effects on prostate, cervix, brain, breast and colon cancers (7). The inhibitory effects of genistein on carcinogenesis and cancer progression have been known for years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Genistein, which is abundantly found in soybean, is anti-proliferative cancer cell. Genistein is a potent inhibitor of tyrosine kinase, which is involved in proliferation signal cascades of cell growth (5), and moderate doses of genistein have been found to have inhibitory effects on prostate, cervix, brain, breast and colon cancers (7). The inhibitory effects of genistein on carcinogenesis and cancer progression have been known for years.…”
Section: Discussionmentioning
confidence: 99%
“…High correlation was seen between genistein and reduction of the growth rate in time-and dose-dependent manner, higher concentrations of genistein and longer treatment periods demonstrated more reduction in growth rate. Increasing the time of exposure to a higher non-toxic dose of genistein could effectively induce its anti-proliferative effect against acute lymphoblastic leukemia (5). Of course, reduction in growth rate in 72 hours could be due to the lack of nutrients in the cell.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in cancer cells, MTA3 is directly regulated by estrogen and estrogen receptor alpha (Erα) binding to its promoter [17]. In the trophoblast cell line, JAR, recent research has shown that over-expression of estrogen receptor beta (ERβ) increased MTA3 expression and decreased expression of its target gene, Snail [18]. Furthermore, dys-regulation of estrogen and ERα expression has been reported in preeclamptic placenta [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…MTA3 is most well-studied in breast cancer, where it has been identified as a key link between estrogen receptor status and tumor invasion [6]. MTA3 has also been implicated in regulation of trophoblast invasion, downstream of estrogen receptor signaling [7]. Expression of MTA3 is also reportedly decreased in preeclampsia [8].…”
Section: Introductionmentioning
confidence: 99%